Coronary risk in relation to genetic variation in MEOX2 and TCF15 in a Flemish population. Issue 1 (December 2015) - Yang, Wen-Yi; Petit, Thibault; Thijs, Lutgarde; Zhang, Zhen-Yu; Jacobs, Lotte; Hara, Azusa; Wei, Fang-Fei; Salvi, Erika; Citterio, Lorena; Delli Carpini, Simona; Gu, Yu-Mei; Knez, Judita; et al.
Abstract Background In mice MEOX2/TCF15 heterodimers are highly expressed in heart endothelial cells and are involved in the transcriptional regulation of lipid transport. In a general population, we investigated whether genetic variation in these genes predicted coronary heart disease (CHD). Results In 2027 participants randomly recruited from a Flemish population (51.0 % women; mean age 43.6 years), we genotyped six SNPs inMEOX2 and four inTCF15 . Over 15.2 years (median), CHD, myocardial infarction, coronary revascularisation and ischaemic cardiomyopathy occurred in 106, 53, 78 and 22 participants. For SNPs, we contrasted CHD risk in minor-allele heterozygotes and homozygotes (variant)vs. major-allele homozygotes (reference) and for haplotypes carriers (variant)vs. non-carriers. In multivariable-adjusted analyses with correction for multiple testing, CHD risk was associated withMEOX2 SNPs (P  ≤ 0.049), but not withTCF15 SNPs (P  ≥ 0.29). TheMEOX2 GTCCGC haplotype (frequency 16.5 %) was associated with the sex- and age-standardised CHD incidence (5.26vs . 3.03 events per 1000 person-years;P  = 0.036); the multivariable-adjusted hazard ratio [HR] of CHD was 1.78 (95 % confidence interval, 1.25–2.56;P  = 0.0054). For myocardial infarction, coronary revascularisation, and ischaemic cardiomyopathy, the corresponding HRs were 1.96 (1.16–3.31), 1.87 (1.20–2.91) and 3.16 (1.41–7.09), respectively. TheMEOX2 GTCCGC haplotype significantly improved the prediction of CHD over and beyond traditional risk factors and was associated with similar population-attributable risk as smoking (18.7 %vs. 16.2 %). Conclusions Genetic variation inMEOX2, but notTCF15, is a strong predictor of CHD. Further experimental studies should elucidate the underlying molecular mechanisms.